CONSISTENCY MODEL OF COURT DESIGNATION TO FOSTER PARENT RIGHTS AUTHORITY DUE TO DIVORCE ON CHILDREN - Erna Trimartini (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
This paper is entitled " The Consistency Model of Court Designation to Foster Parent Rights Authority Due to Divorce on Childern" is the result of research competitive grants funded by the Ministry of Research and Technology. This study found a model: "BP4 Friends of Children". BP4 is an Advisory Board, Development, Preservation of Marriage, which has activities that aims to reduce the number of divorces. In the passage of time, the role of BP4 increases, which also carries out advisory couples who file for divorce / divorce in religious court. This activity is considered highly strategic in order to reduce the divorce rate. However, in case they are unsuccessful, then the role of a mediator BP4 needs to be optimized for husband and wife to make children care power of attorney agreement. Results of power agreement children custody rights set forth in the minutes that can be used as the basis for the judge in making the determination of rights of custody of the children's power of divorce. Therefore, it is necessary to provide strengthening the role of BP4. The reinforcement is in the form of policy formulation "BP4 Friends of Children", which regulates BP4 role as a mediator for a husband and wife who file for divorce / divorce in making children care power of attorney agreement. Keywords: BP4 Friends of Children, children care power of attorney.